Effects of vermicompost leachate on nitrogen, phosphorus, and microbiome in a food waste bioponic system. (1st August 2023) - Wongkiew, Sumeth; Polprasert, Chongrak; Noophan, Pongsak (Lek); Koottatep, Thammarat; Kanokkantapong, Vorapot; Surendra, K.C.; Khanal, Samir Kumar
Abstract: Food waste is rich in nutrients, such as nitrogen and phosphorus, and can be integrated with bioponics, a closed-loop agricultural system that combines hydroponics with biological nutrient recovery. Vermicompost leachate (VCL) supplementation has been shown to improve the co-composting of organic waste (i.e., compost quality) and the biodegradation of organic compounds. Thus, VCL has high potential for enhancing nutrient availability in bioponics from food waste. However, the understanding of nitrogen and phosphorus availability in food waste-based bioponics is limited, both with and without VCL. In this study, food waste derived from cafeteria vegetable waste was used as the substrate (500 g dry wt./system) in bioponics to grow lettuce ( Lactuca sativa L.) for two consecutive cycles (35 days/cycle) without substrate replacement. VCL was applied weekly (1–5% v/v) and compared to the control without VCL. The results showed that the food waste in bioponics provided nitrogen and phosphorus for plant growth (15.5–65.8 g/lettuce head). Organic-degrading and nutrient-transforming bacteria ( Hydrogenispora, Clostridium_sensu_stricto_1, Ruminiclostridium_1, Cellvibrio, Thauera, Hydrogenophaga, and Bacillus ) were predominantly found in plant roots and residual food waste. VCL addition significantly increased nitrate, phosphate, and chemical oxygen demand levels in bioponics, owing to the nutrients in VCL and the enhancement of keystone microorganisms responsible for organic degradation and nutrient cycling (e.g., Ellin6067, Actinomyces, and Pirellula ). These findings suggest that nitrogen, phosphorus, and organic carbon concentrations in an ecosystem of nutrient-transforming and organic-degrading microbes are key in managing nutrient recovery from food waste in bioponics. Graphical abstract: Image 1 Highlights: Degradation of food waste led to available N and P and an increase in COD. Food waste-based bioponics recovered N (11.2%) and P (66%). The bioponics provided a marginal yield of 15.4–65.8 g/lettuce head. VCL supplementation enhanced microbial degradation of food waste. Development of keystone taxa was significantly enhanced by VCL supplementation.